Implementation of Fiduciary Guarantee Execution for Defaulting Debtors After the Decision of The Constitutional Court Number: 18/Puu-Xvii/2019 - Regina Wydya Prameswari; Mhd. Yadi Harahap (Journal Equity of Law and Governance, 2024)
The purpose of this study is to examine the enforcement of fiduciary promises against defaulting debtors following the Constitutional Court ruling Number 18/PUU-XVII/2019. The regulations pertaining to the registration of fiduciary guarantees, which was previously regarded as a necessary prerequisite for the guarantee's validity, were changed by this ruling. Using a library research approach, this study examines numerous legal sources, rules, and relevant literature to comprehend the legal modifications brought about by the decision. The study's primary focus is on the legal ramifications for creditors' and debtors' rights, as well as how the Constitutional Court's decision impacts the process of executing fiduciary assurances against defaulting debtors. The findings indicate that, while the verdict allows for greater flexibility in fiduciary registration, execution confronts procedural and creditor protection issues. In order to provide equitable legal protection for both parties, this study makes suggestions for enhancing the fiduciary guarantee implementation mechanism after the verdict.